Bioactive PLGA polymer nanoparticle loaded gels for atopic dermatitis treatment - Eun Ju Park; Belle Lin Hwee Yap; Xinning Wang; Qi Zhen Poh; Chee Hian Tan; Li Fang Koh; John E. Common; Peili Teo (Discover Applied Sciences)
Abstract Atopic dermatitis (AD) is a major chronic inflammatory skin disease that causes itching, redness and irritation. Categorized as the largest skin disability, it poses a substantial financial and social burden on patients. In this study, we report on the synthesis and characterization of arginyl-glycyl-aspartic acid (RGD) and hyaluronic acid (HA) conjugated amphiphilic bioactive PLGA brush block copolymer, poly(lactic-co-glycolic acid)-b-poly(ethylene glycol)RGD (PLGA-b-PEGRGD) and poly(lactic-co-glycolic acid)-b-poly(ethylene glycol)HA (PLGA-b-PEGHA), and amphiphilic bioactive PLGA homopolymers, poly[poly(lactic-co-glycolic acid)-poly(ethylene glycol)-RGD] P(PLGA-PEG-RGD) and poly[poly(lactic-co-glycolic acid)-poly(ethylene glycol)-HA] P(PLGA-PEGR-HA) via ring opening metathesis polymerization (ROMP). Bioactive PLGA polymer nanoparticles are prepared using a reprecipitation method. The nanoparticles were formulated into gel form using hydroxyethyl cellulose (HEC) as gelling agent and phosphate buffered saline (PBS, pH 7.4) as medium for further biocompatibility test. The size and morphology of nanoparticles are determined using dynamic light scattering (DLS) and scanning electron microscopy (SEM) imaging. The bioactive PLGA nanoparticles loaded gels demonstrated good biocompatibility from ex vivo 3D human skin model studies. In vivo studies using MC-903 induced AD mouse models showed effective inflammation reduction and improved skin barrier repair using our PLGA-RGD nanoparticle loaded gel compared to hydrocortisone as a positive control. We demonstrate here the potential of using these bioactive PLGA nanoparticles for treatment of atopic dermatitis or skin inflammation conditions. Graphical abstract